2015
DOI: 10.4137/ehi.s29431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UV–H2O2 Advanced Oxidation and Aging Processes on GAC Capacity for the Removal of Cyanobacterial Taste and Odor Compounds

Abstract: Cyanobacteria and their taste and odor (T&O) compounds are a growing concern in water sources globally. Geosmin and 2-methylisoborneol (MIB) are the most commonly detected T&O compounds associated with cyanobacterial presence in drinking water sources. The use of ultraviolet and hydrogen peroxide (H2O2) as an advanced oxidation treatment for T&O control is an emerging technology. However, residual H2O2 (>80% of the initial dose) has to be removed from water prior final disinfection. Recently, granular activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Hydrogen peroxide was able to oxidize up to the odor threshold with the maximum dose (1.5 mg/l), when using only the conventional treatment without the application of polymer in the treatment. However, any residual oxidant must be fully removed before the disinfection process, as it exerts a strong chlorine demand and could compromise final disinfection, leading to insufficient chlorine residual within the distribution system (Zamyadi et al 2015b). Xu et al (2019) found that the concentration of 2-MIB decreased with the application of doses between 3.0 and 20.0 mg/l H 2 O 2 after 8 h of reaction, showing that the capacity of H 2 O 2 to eliminate 2-MIB was greater than that of CuSO 4 and KMnO 4 .…”
Section: Oxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide was able to oxidize up to the odor threshold with the maximum dose (1.5 mg/l), when using only the conventional treatment without the application of polymer in the treatment. However, any residual oxidant must be fully removed before the disinfection process, as it exerts a strong chlorine demand and could compromise final disinfection, leading to insufficient chlorine residual within the distribution system (Zamyadi et al 2015b). Xu et al (2019) found that the concentration of 2-MIB decreased with the application of doses between 3.0 and 20.0 mg/l H 2 O 2 after 8 h of reaction, showing that the capacity of H 2 O 2 to eliminate 2-MIB was greater than that of CuSO 4 and KMnO 4 .…”
Section: Oxidantsmentioning
confidence: 99%
“…GSM and 2-MIB are compounds that are difficult to remove with conventional water treatment processes, such as coagulation, sedimentation, and filtration; only advanced water treatment processes can be considered as alternative methods to remove GSM and 2-MIB. The processes reported by different authors include oxidation (Park et al 2006), adsorption of activated carbon (Cook et al 2001;Zamyadi et al 2015a;Bong et al 2021), nanofiltration (Dixon et al 2011), and ultraviolet rays with H 2 O 2 (or TiO 2 ) (Rosenfeldt et al 2005;Zamyadi et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 HABs affect drinking water and wastewater treatment plants by requiring additional pre-treatment or treatment activity; or in extreme cases, by plant closures as a result of treatment failure. 8 10 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 HABs affect drinking water and wastewater treatment plants by requiring additional pre-treatment or treatment activity; or in extreme cases, by plant closures as a result of treatment failure. [8][9][10] Within freshwaters, cyanobacteria (also termed blue-green algae), are a major concern. Although blooms have been reported under a broad range of environments, 11 cyanobacteria are most likely to proliferate under warm, calm, and nutrientrich conditions.…”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, it can react with chlorine, if chlorine is used as disinfectant in downstream process, compromising disinfection before distribution and increasing costs. 25 Therefore, management of H 2 O 2 residual was also investigated in order to establish a more efficient and effective integrated technology for potential field application of sulfolane groundwater remediations. system.…”
Section: Introductionmentioning
confidence: 99%